TOPORIŠIČEVO LETO (11. 10. 2015–11. 10. 2016) - Kus, Mateja; Majce, Irena (Slavia Centralis, 2020)
The article describes the course of activities that took place in Toporišič’s year (11 October 2015–11 October 2016).